Study the failure of casted copper anode: The formation of bumps defects on the surface of the anode during casting. (August 2022) - Reza Shojaei, Mohammad; Reza Khayati, Gholam; Javad Khorasani, Seyed Mohammad; Assadat Yaghubi, Nahid
Highlights: Selection of the failure of casting anode as a real case study. Proposed the mechanism of failure based on the metallurgical approach. Study the effect of impurities in the formation of bumps of casting anode. Defined the role of gas bubbles in the formation of anodes bumps. Abstract: Copper anode (∼98%) is widely used to produce the cathode (99.995 wt%) in electrorefining process. These anodes sometimes become problematic from the production line due to the presence of bumps/holes on their surface. To find the reason of this defect, chemical composition of the three casted anodes was determined by the quantmeter analysis. Also, the microscopic and phase analysis were done by FESEM, EDS, XRD, and XRF for three types of anodes bump. The chemical analysis of anodes confirmed a high level of sulfur and oxygen, which have a key role in the formation of bumps. The results confirmed the presence of impurities including Cu2 S, BaSO4, CaCO3 and MgCO3, which cause the formation of gas bubbles at the final stage of solidification. The main source of these impurities was barium sulfate as mold covering and magnesia-chrome bricks (as refractories). To prevent bumps phenomena, the control of impurities content is necessary.